PENINGKATAN KREATIVITAS ANAK USIA DINI MELALUI PEMBELAJARAN TERPADU BERBASIS KECERDASAN JAMAK - ASMAWATI, LULUK (Program Studi Magister Pendidikan Anak Usia Dini, 2017)
The objective of this research was the improvement of creativity of early childhood by applying integrated based on learning model of multiple intelligences. The research was conducted at Taman Kanak-kanak Aisyiyah 10 Depok. This research used the action research methods of Kemmis Taggart model. The qualitative data were analyzed using inductive process involving reduction of information after being organized into important themes and components. The quantitative data were analyzed using descriptive statistics to measure creativity scores of the same groups. The research findings were as follows: (1) there was improvement on the following aspects: learning situation, student involvement during practical work and activities and also on the student teamwork, (2) there was a difference between pre and post assessment of students’ creativity in four dimensions, such as fluency, flexibility, originality, and elaboration, (3) creativity of early childhood can be improved by applying simple and practical steps as far as integrated based learning of multiple intelligences was concerned, (4) through stimulation of creativity learning, students’ creativity can be improved eight times as high as those who do not experience such a stimulation. It can be concluded that integrated based learning of multiple intelligences was one of strategy to improve creativity for early childhood. Keywords: creativity, early childhood, integrated learning based on multiple intelligences